Pacific Currents The Responses of U.S. Allies and Security Partners in East Asia to China's Rise - Medeiros, Evan S. (RAND Corporation, 2008)
China's importance in the Asia-Pacific has been on the rise, raising concerns about competition the United States. The authors examined the reactions of six U.S. allies and partners to China's rise. All six see China as an economic opportunity. They want it to be engaged productively in regional affairs, but without becoming dominant. They want the United States to remain deeply engaged in the region.